2022
DOI: 10.1038/s41434-022-00317-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dystrophin carboxy-terminal domain for micro-dystrophin gene therapy in cardiac and skeletal muscles in the DMDmdx rat model

Abstract: Duchenne muscular dystrophy (DMD) is a muscle wasting disorder caused by mutations in the gene encoding dystrophin. Gene therapy using micro-dystrophin (MD) transgenes and recombinant adenoassociated virus (rAAV) vectors hold great promise. To overcome the limited packaging capacity of rAAV vectors, most MD do not include dystrophin carboxy-terminal (CT) domain. Yet, the CT domain is known to recruit α1-and β1-syntrophins and α-dystrobrevin, a part of the dystrophin-associated protein complex (DAPC), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…The protein samples used as positive controls in the dystrophin western-blot were obtained from rat pectoral muscle biopsies from a previous study. 73 Dmd mdx rats and healthy controls were handled and housed in the UTE IRS2 from Nantes Université, according to a protocol approved by the Institutional Animal Care and Use Committee of the Région des Pays de la Loire (University of Angers, France) as well as the French Ministry for National Education, Higher Education and Research (authorization #2018102616384887).…”
Section: Methodsmentioning
confidence: 99%
“…The protein samples used as positive controls in the dystrophin western-blot were obtained from rat pectoral muscle biopsies from a previous study. 73 Dmd mdx rats and healthy controls were handled and housed in the UTE IRS2 from Nantes Université, according to a protocol approved by the Institutional Animal Care and Use Committee of the Région des Pays de la Loire (University of Angers, France) as well as the French Ministry for National Education, Higher Education and Research (authorization #2018102616384887).…”
Section: Methodsmentioning
confidence: 99%
“…Rat Muscle biopsies: The protein samples used as positive controls in the dystrophin western-blot were obtained from rat pectoral muscle biopsies from a previous study 58 . Dmd mdx rats and healthy controls were handled and housed in the UTE IRS2 from Nantes Université, according to a protocol approved by the Institutional Animal Care and Use Committee of the Région des Pays de la Loire (University of Angers, France) as well as the French Ministry for National Education, Higher Education and Research (authorization #2018102616384887).…”
Section: Experimental Model and Study Participant Detailsmentioning
confidence: 99%
“…The authors also indicated that the expression of micro-dystrophin in mdx 5cv mice prevented the development of cardiac histopathology but did not rescue membrane localization of cavins nor did it normalize ERK signaling ( 93 ). Bourdon et al ( 94 ) recently showed in DMD mdx rats that the ΔR4-23/ΔCT expression is sufficient to restore the interactions of most dystrophin associated protein complex (DAPC) partners in skeletal and cardiac muscles. In contrast, the addition of C terminal domain significantly increases the restoration of that interaction.…”
Section: Molecular Biology Approaches For Duchenne Muscular Dystrophymentioning
confidence: 99%